A phylogeny of fossil and living neocoleoid cephalopods. (11th August 2015) - Sutton, Mark; Perales‐Raya, Catalina; Gilbert, Isabel
Abstract: Coleoid cephalopod phylogeny is well studied via both molecular and morphological data, yet although some agreement has been reached (e.g. that extant Decapodiformes and Octopoda are monophyletic) many details remain poorly resolved. Fossil coleoids, for which much data exists, have hitherto not been incorporated into analyses. Their inclusion is highly desirable for the support of neontological phylogenies, to better reconstruct character‐state histories, and to investigate the placement of the fossil groups themselves. In this study we present and analyse a morphological data matrix including both extinct and extant taxa. Homology assumptions in our data are discussed. Our results are presented both with and without the constraint of a monophyletic Decapodiformes imposed. When analysed with this constraint our results are strikingly congruent with those from molecular phylogeny, for instance placing Idiosepius in a basal position within Decapodiformes, and recovering Oegopsida and Bathyteuthoidea (although as grades). Our results support an Octopodiformes clade ("vampire squid" Vampyroteuthis as sister to Octopoda) and an octopodiform interpretation for most fossil coleoids. They suggest the fossil sister taxon to the octopods to be Plesioteuthididae. Most fossil higher taxa are supported, although many genera, especially within suborder Teudopseina, appear para‐ or polyphyletic.